Comparative Study of Mechanical Properties and Thermal Stability on Banyan/Ramie Fiber-Reinforced Hybrid Polymer Composite. (17th December 2021) - Raja, T.; Ravi, S.; Karthick, Alagar; Afzal, Asif; Saleh, B.; Arunkumar, M.; Subbiah, Ram; Ganeshan, P.; Prasath, S.
Abstract : The usage of natural fibers has increased recently. They are used to replace synthetic fiber products in aircraft and automobile industries. In this study, natural fibers of bidirectional banyan mat and ramie fabrics are used for reinforcement, and the matrix is an epoxy resin to fabricate composite laminates by traditional hand layup technique at atmospheric temperature mode. Five different sequences of reinforcements are as follows to quantify the effect of thermal stability and mechanical behavior of silane-treated and untreated hybrid composites. The results revealed that silane-treated fabric composite laminates were given enhanced mechanical properties of 7% tensile, 11% flexural, and 9% impact strength compared with untreated fabric composite, and at the same time when the increasing of ramie fabric was given the positive influence of 41% improved tensile strength of 40.7 MPa, 49% improved in flexural strength of 38.9 MPa and negative influence in 57% lower impact strength in sample E and positive value in sample A 21.12 J impact energy absorbed in the hybrid composite. Thermogravimetric analysis (TGA) revealed the thermal stability of the hybrid composite. In sample A, the thermal stability is more than in other samples, and 410°C is required to reduce the mass loss of 25%. The working mass condition of the hybrid composite is up to 3.25 g after it moves to degrade.